Controlled synthesis of graphite oxide: Formation process, oxidation kinetics, and optimized conditions. (2nd February 2018) - Li, Chang; Shi, Yexun; Chen, Xi; He, Dafang; Shen, Liming; Bao, Ningzhong
Graphical abstract: Highlights: The oxidation process of FG is expressed by the one-half-order kinetic model R2. The diffusion rate of MnO3 + and the oxidation rate of FG are discovered to be constant. The transformation of functional groups during FG oxidation is described. The chemical composition and defect extent of GO is adjustable using reaction conditions. Abstract: Graphite oxide (GO) is one of the most extensively studied materials and has been tested for numerous applications due to its unique properties. Nevertheless, a quantitative description of complicated transfer and reaction rates of the oxidation of graphite is still not available, which essentially hinders large-scale production of high-quality GO and other graphene related materials. In this work, GO is prepared from flake graphite (FG) by a modified Hummers method. Size and color evolutions of time-dependent complementary domains, i.e. the starting GO domain and the remaining FG domain, are monitored during the entire oxidation process. The oxidation of FG in acidic oxidizing medium can be interpreted as a contracting area process controlled by phase boundary. Reaction rate constant ( k ) and kinetic parameters ( Ea, ln  A ) are obtained after a systematic investigation of the influence of reaction temperature, concentration of sulfuric acid, and oxidizing agent on the oxidation, with the aid of R2 mathematical model. Using the kinetic results, the oxidation process and the conversion rate from FG to GO thus become controllable. Both intermediate products and final GO products are studied using XRD, TGA, and XPS to reveal the oxidation mechanism. The degree of oxidation of FG and the content of major functional groups on the surface of products can thus be optimized. Our research results are valuable to understanding fundamental mechanism of graphite oxidation and to achieving industrial production of high-quality GO with controllable degree of oxidation and tunable proportion of oxygen-containing functional groups for a variety of applications.